Beliefs and attitudes of barcelonians towards chilean variety - Illamola, Cristina; Forment Fernández, Mar (Lenguas Modernas, 2023)
This study presents the main results on beliefs and attitudes of a stratified sample of 144 informants from Barcelona towards the Chilean variety. Based on the methodology of the Project for the study of beliefs and attitudes towards Spanish varieties in the XXI century (PRECAVES XXI), the results review whether the existence of a “better Spanish” is still valid. Then, it examines the degree of identification of the different varieties of Spanish by participants from Barcelona and, finally, a set of questions, grouped into direct evaluations (cognitive and affective) and indirect evaluations (sociocultural features of the speaker, the country and its culture), are examined to observe attitudes and beliefs towards the Chilean variety. In general, the ratings are positive and, for social factors (gender, age, level of education and L1) and extralinguistic factors (male or female voice) that may explain the differences between groups, the participant’s L1 (Spanish or Catalan), as well as the voice heard (a male or a female voice) should be noted.